2020
DOI: 10.1108/sasbe-06-2019-0082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of landslide area of Tulung subdistrict, Ponorogo, Indonesia in 2017 using resistivity method

Abstract: PurposeResearch has been conducted to analyze the landslide in Banaran area, Ponorogo Regency. The landslides occurred on April 1, 2017. This study was conducted to know the subsurface conditions in the Banaran area to analyze the disaster mitigation efforts. The mitigation efforts are made to reduce the risk from landslides and possible landslides.Design/methodology/approachThe method used is the geo-electric resistivity method of Wenner–Schlumberger configuration. The research was conducted in three villages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The injected current spreads under the surface, from which potential difference values measured by M and N potential electrodes are obtained. The field data acquisition process uses Schlumberger configuration due to its efficiency and error minimal [11]. The working principle of this configuration is shown by Figure 1, which shows that distance between MN potential electrodes is closer, while the distance of current electrodes is changed gradually according to the predetermined lane length.…”
Section: Methodsmentioning
confidence: 99%
“…The injected current spreads under the surface, from which potential difference values measured by M and N potential electrodes are obtained. The field data acquisition process uses Schlumberger configuration due to its efficiency and error minimal [11]. The working principle of this configuration is shown by Figure 1, which shows that distance between MN potential electrodes is closer, while the distance of current electrodes is changed gradually according to the predetermined lane length.…”
Section: Methodsmentioning
confidence: 99%
“…Three case studies which we have been discussed showed that resistivity method was approriate for mitigating hydrometeorological disaster. For further analysis, we comparing withresistivity data from landslide disaster area in Pulung Subdistrict, Ponorogo in 2017 [19]. From 12 resistivity measuring points in the area, it was identified rock with resistivity ranging(1.4-67.5)Ωm which were interpreted as clay, tuff lapili, volcanic breccia, and andesite lava.…”
Section: Aquifer Exploration For Drought Disaster Mitigation In Tulungagungmentioning
confidence: 99%
“…The resistivity cross-section can be used to identify rock layers and the direction of the subsurface structure [18]. Many additional geoelectrical resistivity studies have been conducted to prevent geological disasters, such as identifying structures (faults) and subterranean lithology that can trigger geological disasters [19][20][21].…”
Section: Introductionmentioning
confidence: 99%